Diagnoza i postępowanie logopedyczne w nauczaniu języka polskiego jako obcego - Czempka-Wewióra, Maria; Graboń, Karolina (Postscriptum Polonistyczne, 2020)
The article describes how to use the competence of a speech therapist in teaching Polish as a foreign language (especially at the early stage of the glottodidactic process). Teaching pronunciation is an integral element of teaching Polish as a foreign language and according to the authors of the article, it can be more effective if the following issues are taken into consideration: diagnosis of speech disorders (including efficiency of speech organs and phonemic hearing) and an efficient therapy. Such an approach is advised in the case of students: 1. who have no biological deficits, however have problems learning correct pronunciation; 2. who have speech defects; or 3. whose pronunciation in a learnt language is influenced by speech therapy.